PENGARUH KOMPETENSI, INDEPENDENSI, AKUNTABILITAS, PENGALAMAN KERJA DAN ETIKA AUDITOR TERHADAP KUALITAS AUDIT PADA KAP DI SEMARANG - Devi, Aneta; Srimindarti, Ceacilia (2021)
The purpose of this study is examine the influence of competence, independence, accountability, work experience, and auditor code of ethics on audit quality Public Accounting Firm in Semarang.This study includes quantitative research with a population of auditors at Public Accounting Firm in Semarang with a research sample of 85 auditors. Data was collected using questionnaires, interviews, and documentation. The data analysis method used is multiple regression analysis using SPSS 26. The results of the research data analysis showed that the results of testing the influence of the Competency variable on Audit Quality obtained a sig value of 0.038. The results show that the independence obtained a sig value of 0.008. The accountablity obtained a sig value of 0.025. The work experience obtained a sig value of 0.016. The auditor code of ethics obtained a sig value of 0.035. These results competence, independence, accountability, work experience and auditor ethics have a positive impact on audit quality at the Public Accounting Firm in Semarang.